2013
DOI: 10.1017/s0958344013000049
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the “CoDe”: a framework for conceptualizing and designing help options in computer-based second language listening

Abstract: This paper proposes a theoretical framework for the conceptualization and design of help options in computer-based second language (L2) listening. Based on four empirical studies, it aims at clarifying both conceptualization and design (CoDe) components. The elements of conceptualization consist of a novel four-part classification of help options: operational, regulatory, compensatory and explanatory. The design section establishes ways that make help options easy to use, encourage learner control, frame guida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 53 publications
(105 reference statements)
0
11
0
Order By: Relevance
“…In their study, Webb and Rodgers analyzed the transcripts of 88 television programs of different genres (e.g., news, drama) and found that learners need a vocabulary size of 2,000 to 4,000 word families (including proper nouns and marginal words) for a 95% coverage 1 , which is required for adequate comprehension (Nation, 2006). Yet one of the advantages of using CALL and multimedia environments is that the environments might include different types of help options (Ca´rdenas-Claros & Gruba, 2013) such as paced audio delivery and on-screen text. Factors such as the speed of the input and the presence of low-frequency words (Webb, 2010) make listening a particularly challenging skill for L2 learners.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study, Webb and Rodgers analyzed the transcripts of 88 television programs of different genres (e.g., news, drama) and found that learners need a vocabulary size of 2,000 to 4,000 word families (including proper nouns and marginal words) for a 95% coverage 1 , which is required for adequate comprehension (Nation, 2006). Yet one of the advantages of using CALL and multimedia environments is that the environments might include different types of help options (Ca´rdenas-Claros & Gruba, 2013) such as paced audio delivery and on-screen text. Factors such as the speed of the input and the presence of low-frequency words (Webb, 2010) make listening a particularly challenging skill for L2 learners.…”
Section: Introductionmentioning
confidence: 99%
“…Factors such as the speed of the input and the presence of low-frequency words (Webb, 2010) make listening a particularly challenging skill for L2 learners. Yet one of the advantages of using CALL and multimedia environments is that the environments might include different types of help options (Cárdenas-Claros & Gruba, 2013) such as paced audio delivery and on-screen text. In the remainder of this paper, we focus on the potential of captions, i.e., same-language or intralingual subtitles, for supporting L2 learners’ comprehension of audiovisual documents.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the researcher may examine training in help options which facilitates task completion and promotes learning within a framework of the metacognitive listening processes of planning, problem-solving, monitoring, and evaluation. Furthermore, earlier in this section I mentioned Cárdenas-Claros & Gruba's (2013) proposed conceptualisation of listening help-option types and general guidelines. As I stated in the introduction, help-option researchers rarely integrate mainstream L2 listening theory (e.g., metacognition, listening strategies, skills-based listening) into their research, instead focusing on interactionist theories, for instance.…”
Section: Research Agendamentioning
confidence: 99%
“…Reflecting on the issue that participants were rarely using some help options to facilitate their learning in her study, Liou (1997) raised the matter of determining whether listeners are being provided with more help options than are necessary or whether they have optimised their help-option use down to a few key choices. Furthermore, Cárdenas-Claros & Gruba's (2013) proposed framework for conceptualising L2 listening help options and associated design guidelines is in need of further examination and could usefully form the theoretical basis and guiding principles for this kind of research task. Lastly, Cárdenas-Claros & Gruba (2014) used Longman English Interactive (Rost & Fuchs 2004, LEI © 2008), an off-the-shelf product designed for language learners with built-in help options.…”
Section: Research Agendamentioning
confidence: 99%
See 1 more Smart Citation